Sudden cardiac death due to physical exercise in male competitive athletes. A report of six cases - Durakovic, Z.; Misigoj-Durakovic, M.; Vuori, I.; Skavic, J.; Belicza, M. (The Journal of Sports Medicine and Physical Fitness, 2005)
In the period of 30 years, i.e. from 1973 to 2002, we noticed in Croatia 6 sudden and unexpected cardiac deaths in male athletes during or after training. Two were soccer players, 2 athletic runners, one was a rugby player and one was a basketball player. All of them were without cardiovascular symptoms. At the forensic autopsy, the first athlete, aged 29, had chronic myocarditis and thickened left ventricular wall of 15 mm. The second, aged 21, had an acute myocardial infarction of the posterior wall with normal coronaries and thickened left ventricular wall of 15 mm. The third aged 17, had hypoplastic right coronary artery and narrowed ascending aorta, suppurant tonsillitis and subacute myocarditis. Two athletes, aged 29 and 15, had hypertrophic cardiomyopathy and normal coronaries, and one dilated aorta. The sixth, aged 24, had arrhythmogenic cardiomyopathy of the right ventricle. All the 6 athletes died suddenly, obviously because of malignant ventricular arrhythmias. In Croatia the death rate among athletes reached 0.15/100 000, in others who practice exercise reached 0.74/100 000 and the difference is highly significant (c2=14.487, Poisson rates=3.81, P=0.00014) and in physicians-specialists reached 33.6/100 000. Preventive medical examinations are essential, especially in athletes before physical exercise, as are other investigations in every case suspicious of heart disease, including electrocardiogram (ECG), stress ECG, echocardiography and stress-echocardiography and other findings if indicated. Physical exercise is contraindicated in acute respiratory infection: in 2 of those cases had been a cause of death as a trigger.